L’EFFET TOXIQUE D’UN MELANGE D’HUILLES VEGETALES SUR LES LARVES L3 DE MOUSTIQUES - Djebbari Radhia; Remadnia Ouissem (My University, 2023)
This study aims to test the effect of mixtures of essential oils of (Artemisia herba-alba + Ocimum basilicum), (Artemisia herba-alba + Ziziphus spina-christi), (Ziziphus spina-christi + Ocimum basilicum) and (Artemisia herba-alba + Ziziphus spina-christi + Ocimum basilicum)at different concentrations on newly exuviated L3 larvae of Culex pipiens under laboratory conditions and according to the recommendations of the World Health Organization (WHO). The results show a variable sensitivity of the larvae; this sensitivity is even higher with the increase of the oil concentration. Moreover, the toxicity is well marked when the duration of exposure of the larvae is longer. The comparison between the:  Two Mixture (Ziziphus spina-christi and Ocimum basilicum)and (Ziziphus spina-christi and Artemisia herba-alba) shows that the Mixture (Ziziphus spina-christi and Ocimum basilicum) is the most effective.  Two Mixture (Artemisia herba-alba + Ocimum basilicum) and (Ziziphus spina-christi and Artemisia herba-alba) shows that the Mixture (Ziziphus spina-christi and Artemisia herba-alba) is the most effective.  Two Mixtures (Ziziphus spina-christi+Artemisia herba-alba+ Ocimum basilicum) and (Ziziphus spina-christi and Artemisia herba-alba) show that the Mixture (Ziziphus spina-christi+Artemisia herba-alba+ Ocimum basilicum) is the most effective.  Two Mixture (Artemisia herba-alba + Ocimum basilicum) and (Ziziphus spina-christi and Ocimum basilicum) shows that the Mixture (Ziziphus spina-christi and Ocimum basilicum) is the most effective.  Two Mixtures (Ziziphus spina-christi+Artemisia herba-alba+ Ocimum basilicum) and (Ziziphus spina-christi and Ocimum basilicum) shows that the Mixture (Ziziphus spina-christi+Artemisia herba-alba+ Ocimum basilicum) is the most effective.  Two Mixture (Artemisia herba-alba + Ocimum basilicum) and (Ziziphus spina-christi+Artemisia herba-alba+ Ocimum basilicum) shows that the Mixture (Ziziphus spina-christi+Artemisia herba-alba+ Ocimum basilicum) is the most effective.  All mixtures (Artemisia herba-alba + Ocimum basilicum), (Artemisia herba-alba + Ziziphus spina-christi), (Ziziphus spina-christi + Ocimum basilicum) and (Artemisia herba-alba + Ziziphus spina-christi + Ocimum basilicum)watched that the mixture (Ziziphus spina-christi + Ocimum basilicum) isthe most efficient. The toxicological tests carried out, revealed the larvicidal activity of these mixtures. Moreover, the mixture (Ziziphus spina-christi + Ocimum basilicum) is the most effective compared to the other mixtures. ---------------------------------------------------------------------------------------------------------------------------------------------------------------- يهـدف هذا العمل إلى تقديــر نسب التأثير السمي بعد المعاملة ليــرقات الطور الثالث لبعوض Culex pipiens بتـراكيز مختلفــة من مزيج (الشيح + الحبق)، (الشيح + السدر)، (السدر + الحبق) و (الشيح + السدر+ الحبق) وهذا تحت الظروف المخبرية وتوصيات المنظمة العالمية للصحة (OMS) النتائج بينت وجود حساسية كبيرة لليرقات المعاملة مع زيادة التركيز لهذه الامزجة ، كذلك السمية تزداد كلما كانت مدة المعاملة أطـــول كذلك المقارنة بين:  مزيجا (السدر و الحبق ) و (السدر و الشيح) بينت ان مزيج (السدر و الحبق ) هو الاكثر فعالية .  مزيجا (الشيح و الحبق ) و (السدر و الشيح) بينت ان مزيج (السدر و الشيح الابيض) هو الاكثر فعالية.  مزيجا (السدر , الحبق و الشيح الابيض ) و (السدر و الشيح الابيض) بينت ان مزيج (السدر , الحبق و الشيح الابيض ) هو الاكثر فعالية.  مزيجا (الشيح و الحبق) و (السدر و الحبق ) بينت ان مزيج (السدر و الحبق) هو الاكثر فعالية  مزيجا (السدر , الحبق و الشيح ) و (السدر و الحبق) بينت ان مزيج (السدر , الحبق و الشيح الابيض )هو الاكثر فعالية.  مزيجا (الشيح و الحبق) و (السدر , الحبق و الشيح) بينت ان مزيج (السدر , الحبق و الشيح الابيض) هو الاكثر فعالية.  جميع الأمزجة (الشيح + الحبق)، (الشيح + السدر)، (السدر + الحبق) و (الشيح + السدر + الحبق) بينت أن مزيج (السدر + الحبق) كان أكثر فعالية من بقية الأمزجة المعامل بها. اختبارات السمية التي أجريت بينت ان هذه الامزجة تملك خصائص مبيد حشري ، وان مزيج (السدر و الحبق) هو الفعال مقارنة ببقية الامزجة. -----------------------------------------------------------------------------------------------------------------------------------------------------------------